Karnataka Annual Plan 1979-80 Volume III Tribal Sub-Plan - Planning Commission (Planning Commission, 1979)
The population of Scheduled Tribes in Karnataka according to 1971 census is 2,31,268 as against the total population of 1,92,096 in 1961 . There is an increase of about 20.14 per cent during the decade. the percentage of Scheduled Tribes population of the State works out to 0.8 per cent. The percentage of literacy among Scheduled Tribes according to 1971 census 14.69 as against the general literacy percentage of 31.54.
Planning Department Government of Karnataka